Potential of the bocachico Prochilodus magdalenae culture with biofloc technology (Orinoquia, 2021)
Prochilodus magdalenae is an endemic species of Colombia, it is considered the main species of the Colombian continental fishery due to its catch volumes and relevance for the fishermen’s economy. It is considered an important species for fish farming to food safety. However, due to its feeding habit (iliophagous detritivore) the farming methods is carried out at low stocking densities (
Keywords: growth; native fish; fish culture; survival; sustainability